2018
DOI: 10.1186/s12893-018-0450-z
|View full text |Cite
|
Sign up to set email alerts
|

Synovial cysts of the hip joint: a single-center experience

Abstract: BackgroundSynovial cyst of the hip joint is a rare clinical condition in need of evidence-based guidelines for its diagnosis and management. Normally, synovial cyst of the hip joint requires no treatment, but when it intrudes into surrounding structures, various clinical symptoms appear. Because of its rarity, a symptomatic synovial cyst is often confounded with a tumor as a space-occupying lesion or with other diseases, depending on its various clinical presentations. Therefore, guidelines for the precise dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In conclusion, given the rarity of the synovial cyst of the hip joint, more clinical literature is required to guide diagnosis and management. 10 A synovial cyst of the hip joint is usually unilateral, and our case represented the first in the literature of bilateral giant hip cysts, which highlighted the importance to consider such diagnosis in a patient with unexplained pain and oedema of bilateral extremities without prior history of trauma, surgery or any other disorders. A surgical approach should be considered to effectively relieve symptoms and complications from the cyst.…”
mentioning
confidence: 69%
See 2 more Smart Citations
“…In conclusion, given the rarity of the synovial cyst of the hip joint, more clinical literature is required to guide diagnosis and management. 10 A synovial cyst of the hip joint is usually unilateral, and our case represented the first in the literature of bilateral giant hip cysts, which highlighted the importance to consider such diagnosis in a patient with unexplained pain and oedema of bilateral extremities without prior history of trauma, surgery or any other disorders. A surgical approach should be considered to effectively relieve symptoms and complications from the cyst.…”
mentioning
confidence: 69%
“…Also, treating the underlying pathology such as rheumatoid arthritis with prednisone and methotrexate can effectively relieve the symptoms. [8][9][10] However, when the patient develops significant complications due to compression onto the nerve, vein, artery or ureter by the enlarged cyst, invasive interventions are often required that include the options of needle puncture and aspiration or surgical resection. Surgical resection of the synovial cyst is effective to restore normal venous return and relieve symptoms subsequently.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As far as the treatment of the cyst is concerned, total hip arthroplasty has been chosen in most cases in literature. 11 , 13 However, aspiration and drainage under ultrasound or CT guidance remains an option despite the higher chances of regression. 11 It has previously been reported that if the primary disease is RA, effective treatment may reduce the size of the cyst.…”
Section: Discussionmentioning
confidence: 99%